Investigating assay formats for screening malaria Hsp90-Hop interaction inhibitors - Derry, Leigh-Anne Tracy Kim (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2019)
Although significant gains have been made in the combat against malaria in the last decade, the persistent threat of drug and insecticide resistance continues to motivate the search for new classes of antimalarial drug compounds and targets. Due to their predominance in cellular reactions, protein-protein interactions (P-PIs) are emerging as a promising general target class for therapeutic development. The P-PI which is the focus of this project is the interaction between the chaperone heat shock protein 90 (Hsp90) and its co-chaperone Hsp70/Hsp90 organising protein (Hop). Hop binds to Hsp70 and Hsp90 and facilitates the transfer of client proteins (proteins undergoing folding) from the former to the latter and also regulates nucleotide exchange on Hsp90. Due to its role in correcting protein misfolding during cell stress, Hsp90 is being pursued as a cancer drug target and compounds that inhibit its ATPase activity have entered clinical trials. However, it has been proposed that inhibiting the interaction between Hsp90 and Hop may be alternative approach for inhibiting Hsp90 function for cancer therapy. The malaria parasite Plasmodium falciparum experiences temperature fluctuations during vector-host transitions and febrile episodes and cell stress due to rapid growth and immune responses. Hence, it also depends on chaperones, including PfHsp90, to maintain protein functionality and pathogenesis, demonstrated inter alia by the sensitivity of parasites to Hsp90 inhibitors. In addition, PfHsp90 exists as a complex with the malarial Hop homologue, PfHop, in parasite lysates. Consequently, the purpose of this study was to explore P-PI assay formats that can confirm the interaction of PfHsp90 and PfHop and can be used to identify inhibitors of the interaction, preferably in a medium- to high-throughput screening mode. As a first approach, cell-based bioluminescence and fluorescence resonance energy transfer (BRET and FRET) assays were performed in HeLa cells. To facilitate this, expression plasmid constructs containing coding sequences of P. falciparum and mammalian Hsp90 and Hop and their interacting domains (Hsp90 C-domain and Hop TPR2A domain) fused to the BRET and FRET reporter proteins "“ yellow fluorescent protein (YFP), cyan fluorescent protein (CFP) and Renilla luciferase (Rluc) - were prepared and used for HeLa cell transient transfections. The FRET assay produced positive interaction signals for the full-length P. falciparum and mammalian Hsp90-Hop interactions. However, C-domain-TPR2A domain interactions were not detected, no interactions could be demonstrated with the BRET assay and western blotting experiments failed to detect expression of all the interaction partners in transiently transfected HeLa cells. Consequently, an alternative in vitro FRET assay format using recombinant proteins was investigated. Expression constructs for the P. falciparum and mammalian C-domains and TPR2A domains fused respectively to YFP and CFP were prepared and the corresponding fusion proteins expressed and purified from E. coli. No interaction was found with the mammalian interaction partners, but interaction of the P. falciparum C-domain and TPR2A domain was consistently detected with a robust Z' factor value of 0.54. A peptide corresponding to the PfTPR2A domain sequence primarily responsible for Hsp90 binding (based on a human TPR2A peptide described by Horibe et al., 2011) was designed and showed dose-dependent inhibition of the interaction, with 53.7% inhibition at 100 Î¼M. The components of the assay are limited to the purified recombinant proteins, requires minimal liquid steps and may thus be a useful primary screening format for identifying inhibitors of P. falciparum Hsp90-Hop interaction.
Keywords: Antimalarials; Heat shock proteins; Drug interactions; Drug resistance; Plasmodium falciparum; High throughput screening (Drug development); Bioluminescence resonance energy transfer (BRET); Fluorescence resonance energy transfer (FRET)